Citra Produk Negara Dalam Mempengaruhi Pilihan Konsumen Terhadap Produk Dengan Variabel Moderasi Harga - Rendy Ramadhiansa (Jurnal Manajemen Bisnis dan Kewirausahaan, 2019)
This research aims to test consumers' perception towards products produced in developing countries similar to products produced in developed countries. In particular, this research will focus on the role of price moderation as moderator variable in the relation between country's image and product preference by consumers in Indonesia. The framework in this research would be using country product image as independent variable, price as moderating variable, which both would affect product preference as dependent variable. Method used in this research is multiple linear analysis. The outcome of this research is that both country product image and price positively affects product selection.